Synthesis, Characterization of Cr(II), Mn(II), Co(II), Ni(II) and Cu(II) Chelates of Monoprotic Tridentates Possessing N,N,O Moiety - Bhandari, Anil; Sharma, Anju; Choudhary, Vimla; Sharma, Shobha (Asian Journal of Chemistry, 2010)
Solid chelates of Cr(II), Mn(II), Co(II), Ni(II) and Cu(II) with o-(N-pyridine-2-methyl imino) benzoic acid (HPB) and β-(N-pyridine-2-methyl imino) propanoic acid (HPP) have been synthesized and characterized by physico-chemical techniques. The ligand acts as monoprotic, tridentate ligand coordinating through nitrogen and oxygen donor sites. The complexes have 1 : 2 (metal-ligand) stiochiometry, in which the bivalent metal showed six coordination number. Magnetic data coupled with electronic and ligand field parametes suggest an octahedral geometry for these chelates.